Anti‐IgE Monoclonal Antibody (Omalizumab) in Refractory and Relapsing Eosinophilic Granulomatosis With Polyangiitis (Churg‐Strauss): Data on Seventeen Patients. Issue 9 (September 2016) - Jachiet, Marie; Samson, Maxime; Cottin, Vincent; Kahn, Jean‐Emmanuel; Le Guenno, Guillaume; Bonniaud, Philippe; Devilliers, Hervé; Bouillet, Laurence; Gondouin, Anne; Makhlouf, Fatma; Meaux‐Ruault, Nadine; Gil, Helder; et al.
Abstract : Objective: To describe the efficacy and safety of omalizumab, an anti‐IgE monoclonal antibody, in patients with refractory and/or relapsing eosinophilic granulomatosis with polyangiitis (Churg‐Strauss) (EGPA). Methods: We conducted a nationwide retrospective study including EGPA patients who received omalizumab. Response was defined as the absence of asthma and/or sinonasal exacerbations with a prednisone dosage of ≤7.5 mg/day (complete response) or >7.5 mg/day (partial response). Results: Seventeen patients (median age 45 years) received omalizumab for severe steroid‐dependent asthma (88%) and/or sinonasal involvement (18%). After a median follow‐up of 22 months, 6 patients (35%) achieved a complete response, 5 patients (30%) achieved a partial response, and 6 patients (35%) had no improvement. The median Birmingham Vasculitis Activity Score decreased from 2.5 at baseline to 0.5 at 12 months. The median number of exacerbations per month decreased from 1 at baseline to 0 at 12 months, and the median forced expiratory volume in 1 second increased from 63% of the percent predicted at baseline to 85% of the percent predicted at 12 months. The median prednisone dosage decreased from 16 mg/day at baseline to 11 mg/day at 6 months and 9 mg/day at 12 months. Omalizumab was discontinued in 8 patients (47%) during follow‐up, because of remission (12.5%), adverse event despite disease remission (12.5%), refractory disease (25%), or relapse (50%). Relapses included retrobulbar optic neuritis attributable to EGPA in 2 patients and severe asthma flare in 2 others. Conclusion: The results of this study suggest that omalizumab may have a corticosteroid‐sparing effect in EGPA patients with asthmatic and/or sinonasal manifestations, but reducing the corticosteroid dose may also increase the risk of severe EGPA flares, which raises the question of the safety of omalizumab in patients with EGPA.